A case of persistent sciatic artery aneurysm with recurrent embolism. (2019) - Tanaka, Mutsuo; Okamoto, Minoru; Okamoto, Ken; Fukui, Toshihiro
Highlights: Recurrent embolism originated from the persistent persistent sciatic artery aneurysm. Distal bypass was required due to the anomaly position of popliteal artery. Persistent sciatic artery aneurysm is rare, but remember in especially acute limb ischemia. Abstract: Introduction: Persistent sciatic artery (PSA) is a rare congenital vascular anomaly. It has several clinical features with the formation of aneurysms. Among the complications, leg ischemia is severe problem and the management involves revascularization and prevention of recurrence. We herein describe an anatomically annoying case of PSA aneurysm with recurrent embolism that necessitated thrombectomy and bypass surgery. And this work has been reported in line with the SCARE criteria. Case presentation: A 76-year-old woman developed leg embolism twice from PSA aneurysm. PSA was complete type and the popliteal artery ran on the lateral side, which was difficult to approach from the standard medial side. Based on these anatomical conditions, thrombectomy of the posterior-tibial artery (PTA) and femoral-PTA bypass were performed. Additionally, the proximal side of PTA from the anastomosis site was ligated to avoid the recurrence of embolism. Residual PSA aneurysm has not yet been treated, but neither clinical complications nor dilatation have occurred. Discussion: PSA is a rare disease, but should be remember in acute limb ischemia. Clear treatments have not yet been established; therefore, its plans need to be considered based on clinical symptoms and anatomical conditions. Conclusion: Although there were anatomical issues in the present case, thrombectomy and bypass surgery were successful and no complications have occurred one year after surgery.